THE INFLUENCE OF RINCIPALS’ INSTRUCTIONAL LEADERSHIP ON TEACHERS’ PERFORMANCE: A QUANTITATIVE STUDY IN ELEMENTARY SCHOOL OF MRANGGEN DISTRICT, DEMAK REGENCY - Istiqomah; Senowarsito; Harto Nuroso (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The quality of education in elementary schools is strongly influenced by teachers’ performance, which in turn is shaped by school leadership practices. This study aims to examine the influence of principals’ instructional leadership on teacher performance in public elementary schools in Dabin III, Mranggen District, Demak Regency. A quantitative approach with a causal associative design was employed. The population consisted of 139 teachers, with 103 teachers selected as respondents using proportional random sampling. Data were collected through structured questionnaires and analyzed using descriptive statistics and simple linear regression. The results show that principals’ instructional leadership has a positive and statistically significant effect on teacher performance. The regression analysis indicates that instructional leadership explains approximately 29% of the variance in teacher performance, suggesting a moderate influence. These findings imply that principals who effectively supervise instruction, provide academic guidance, and support professional development can enhance teachers’ ability to perform their duties. Strengthening instructional leadership is therefore essential for improving teaching quality and school effectiveness.